Effect Of Production Costs And Sales On The Company’s Net Profit - Leny Suzan; Sausan Nabilah R. (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2020)
One way to obtain optimal profits is to conduct sales activities and reduce costs. Sales have an important role in providing income for the company. Production costs are costs that need to be calculated by the company because the high production costs will have an impact on sales and profits to be obtained. This study aims to determine the effect of production costs and sales on net profit in pharmaceutical sub-sector manufacturing companies listed in the Indonesia Stock Exchange period 2013-2018 both simultaneously and partially. This research uses quantitative research methods. The sample used was 7 research samples in a period of six years to obtain 42 sample units. The results of the research show that simultaneous production costs and sales affect profit. Partially shows that the probability of production costs has a significant positive effect on net profit and sales have no effect on net profit.